Chemical Stabilization of Amorphous Peat Using Cement and Fly Ash at Different Water Additive Ratios - Taib, S. N. L.; Afiqah, I.; Galvinov, Indit (International Journal of Integrated Engineering, 2023)
Peat is a very problematic soil as it is poor in strength. However, previous researchers have proven that the compressive strength of peat can be improved by using various methods of soil improvement including chemical stabilization method. In this study, cement and fly ash and lime were additives used and were mixed with amorphous peat at various water additive ratios. To replicate actual stabilization on site, water additive ratio is proposed as to allow stabilization to be performed at natural water content of the peat. Peat samples were collected from Kampung Endap, Samarahan and mixed at its natural moisture content with cement and with fly ash and lime at different water additive ratios of 3.0, 3.5, 4.0, 4.5 and 5.0. The compressive and bearing strengths of the samples were obtained by the unconfined compressive strength (UCS) test and California Bearing Ratio (CBR) test respectively. The results of the study have shown that there is marginal strength gained after 28 and 56 days of air curing period. The peat samples stabilized with cement at 3.5 water additive ratio recorded the highest value with UCS value of 69.48 kPa after 56 days of curing and 0.52 % for CBR test after 28 days curing period. These strength values obtained are lower compared to published data from previous studies. Different technique of mixing in the laboratory that is mixing peat at its natural water content with varied amount of additives at selected water additive ratio as opposed to mixing at maximum dry density and optimum moisture content that is mostly performed in laboratory contributes to the outcome. However, this study has proven that there is an increase in compressive and bearing strengths of stabilized peat in its natural water content compared to original peat without stabilizer.